2023
DOI: 10.1002/pon.6128
|View full text |Cite
|
Sign up to set email alerts
|

Social support and childhood cancer survivors: A systematic review (2006–2022)

Abstract: Objective: Research has indicated that social support may play a protective role in the face of stress and help children and adolescents cope with the demands and challenges they face on a daily basis during their cancer journey. However, social support tends to reduce over time as survivors overcome their illness despite its ongoing importance even years after treatment has finished. The current review aimed to systematically examine existing evidence on social support in child and adolescent cancer survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This causes serious trauma to the families of the affected children. Research has shown that a positive attitude towards the future can help injured individuals better cope with current traumatic events and improve the negative physical and mental experiences they bring [20]. We conducted a survey among parents and found that their post-traumatic growth is at a moderate level and needs to be improved.…”
Section: Discussionmentioning
confidence: 95%
“…This causes serious trauma to the families of the affected children. Research has shown that a positive attitude towards the future can help injured individuals better cope with current traumatic events and improve the negative physical and mental experiences they bring [20]. We conducted a survey among parents and found that their post-traumatic growth is at a moderate level and needs to be improved.…”
Section: Discussionmentioning
confidence: 95%
“…Pediatric cancer is identified as the second leading cause of death among children aged under 14 years ( Faranoush et al, 2022 ). Globally, approximately 400,000 children (aged 0–19 years) receive a cancer diagnosis each year, with 70% being aged below the age of 15 years ( World Health Organization, 2021 ; Deegan et al, 2023 ). Data from the American Cancer Society indicates that roughly 1 out of every 285 children aged below 20 is diagnosed with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Hashemi et al (2024) on childhood and adolescent cancer in Iran revealed a standardized cancer incidence increase from 129.2 per million in 1999 to 132.3 per million in 2016 ( Hashemi et al, 2024 ). Despite this daunting statistic, advances in cancer care and treatment over the past four decades have contributed to improved survival rates in pediatric oncology ( Deegan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 Family and friends tend to be defined as a major source of support for childhood cancer survivors, while family support is more determined to be a major source in middle-to-late adulthood. 11 Within the review paper previously mentioned, Long and Marsland also highlighted the value of social support and various psychosocial outcomes, such as school re-entry and psychological symptoms. 10 Despite their being limitations in the study, this clarifies that there is value and more research is needed for the concept of social support across many medical conditions in pediatric patients and families.…”
mentioning
confidence: 99%